Pedagogical Technology of Formation the Readiness of Future Managers to Create the Health-Oriented Environment in The Organization: Analysis of Effectiveness - Olga I. ZAVYDIVSKA; Nataliia N. ZAVYDIVSKA; Olena V. KHANIKIANTS; Volodymyr Y. KOVALCHUK; Ivan G. HUL (Communications of International Proceedings, 2021)
The aim of this work is to present the main results of the statistical and probabilistic analysis, which confirm the effectiveness of the implementation of the complementary-integrative pedagogical technology of formation the readiness of future managers to create the health-oriented environment in the organization in the educational process. The experiment of the introduction authors’ complementary-integrative pedagogical technology of formation the readiness of future managers to create the health-oriented environment in the organization into the professional education system of future managers lasted during 2017–2018 years in 10 Ukrainian universities. The students of the control groups (n = 198 persons) were studied according to the standard methodology, and the educational process for the students of the experimental groups (n = 204 persons) was organized using the authors’ technology. The methodology of the study reflects the interrelation between methodological approaches on the philosophical, general scientific and specific scientific principles; methodological and technological levels in the content of the authors’ technology. The numerical values of Pearson’s Criterion    and Student’s -test with 95% probability at the significance level  confirm the validity of the positive shifts in the constituent indices that determine the readiness of the students of the experimental groups to create the health-oriented environment in the organization. The results of correlation analysis confirm the fact, that authors’ technology has shifted the focus of future managers’ professional training toward social significance and human-centricity in management.
Keywords: Statistical and Probabilistic Analysis; Future Managers; Complementary-Integrative Pedagogical Technology; Professional Education; Readiness to Create a Health-Oriented Environment in The Organization.